1996
DOI: 10.1103/physrevb.54.588
|View full text |Cite
|
Sign up to set email alerts
|

Josephson tunneling in high-Tcsuperconductors

Abstract: In this article a macroscopic invariance group describing the superconducting state of a twinned crystal is introduced and shown to provide a useful framework for the discussion of Josephson tunneling in twinned crystals. Josephson tunneling from time-reversal symmetry-breaking states is described and compared with that from time-reversal invariant states for both twinned and untwinned crystals and for both c-axis and basal-plane currents, in a model for orthorhombic Y-Ba-Cu-O. In addition, a ring geometry, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The most probable impression corresponds to a mixed order parameter, as a linear combination of s-and d x 2 Ày 2 -wave components. In the case of YBa 2 Cu 3 O 7Ày such a conclusion supports the observation of non-zero Josephson tunneling currents along all principal crystallographic axes [9].…”
Section: Introductionsupporting
confidence: 68%
“…The most probable impression corresponds to a mixed order parameter, as a linear combination of s-and d x 2 Ày 2 -wave components. In the case of YBa 2 Cu 3 O 7Ày such a conclusion supports the observation of non-zero Josephson tunneling currents along all principal crystallographic axes [9].…”
Section: Introductionsupporting
confidence: 68%
“…However, measurements of microwave induced steps at multiples of hf /2e on the I-V curves of Pb/Ag/YBCO tunnel junctions imply dominant first order tunneling [6]. Therefore the finite c-axis Josephson current has to result from a nonvanishing admixture of the s-wave component to the macroscopic order parameter of YBCO [4]. Two alternatives of how this can take place in the junctions based on twinned YBCO have been discussed in the literature:…”
mentioning
confidence: 99%
“…Namely, the contribution of the s-wave part of the YBCO order parameter to the Josephson coupling between a conventional superconductor (superconductor with a pure s-wave symmetry of the order parameter, for example Pb or Nb) and YBCO should average to zero for equal abundances of the two types of twins in YBCO. In other words, the macroscopic pairing symmetry of twinned YBCO samples should be a pure d-wave [4]. Tanaka has shown that a finite second order Josephson current obtains for a junction between the s-wave and c-axis oriented pure d-wave superconductors [5].…”
mentioning
confidence: 99%
“…The behavior of the current in the grainboundary Josephson junctions inside a superconductor with d x 2 −y 2 -wave pairing symmetry depends on the angles α and β formed between the crystalline axes on both sides of junction and the normal to the junction interface [10]. The dependence of the coefficient of the first term in the formula which describes the current in the junction, I 1 , on the angles α and β, is given by the following expression [11]: I 1 = I S1 cos 2α cos 2β + I S2 sin 2α sin 2β, so that, for example, I 1 reaches the maximum at α = β, and I 1 = 0 when α = 45…”
Section: Resultsmentioning
confidence: 99%